2021
DOI: 10.3390/genes12060914
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Slightly Modulates Lipolysis, Lipogenesis and Expression of Adipokines but Not Glucose Uptake in Rodent Adipocytes

Abstract: Adropin is a peptide hormone which modulates energy homeostasis and metabolism. In animals with diet-induced obesity, adropin attenuates adiposity and improves lipid and glucose homeostasis. Adropin promotes the proliferation of rodent white preadipocytes and suppresses their differentiation into adipocytes. By contrast, the effects of adropin on mature white adipocytes are unknown. Therefore, we aimed to evaluate the effects of adropin on lipolysis, lipogenesis and glucose uptake in white rodent adipocytes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Furthermore, we reported earlier that, in vitro, adropin suppresses differentiation of white preadipocytes into mature adipocytes [ 30 ]. In addition, we showed that by acting on adipocytes adropin induces lipolysis and suppresses lipogenesis [ 31 , 32 ]. Therefore, it is possible that adropin may promote body weight loss by modulating energy expenditure and the morphology/differentiation or function of white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reported earlier that, in vitro, adropin suppresses differentiation of white preadipocytes into mature adipocytes [ 30 ]. In addition, we showed that by acting on adipocytes adropin induces lipolysis and suppresses lipogenesis [ 31 , 32 ]. Therefore, it is possible that adropin may promote body weight loss by modulating energy expenditure and the morphology/differentiation or function of white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As research has already proved the association between lipocalin-2 and obesity and obesity-related CVD, monoclonal anti-lipocalin-2 could be a feasible treatment option. Although the specific therapies targeting visfatin and resistin have not yet been established, recent findings have found an anti-inflammatory factor called “adropin” and have been speculated as the antagonist to suppress the mRNA level of these two adipokines [ 212 , 213 ] which might become a potential therapeutic strategy to reduce obesity and obesity-related CVD in both males and females.…”
Section: Role Of Adipokines In Causing Obesity-related Cvdmentioning
confidence: 99%
“…Moreover, the treatment of obese mice with exogenous adropin resulted in improvement of insulin sensitivity and glucolipid metabolism, with lower expression of lipogenic genes in the liver [10]. Adropin regulates the expression of some of the key adipokines, such as adiponectin, resistin and visfatin [48]. Although, the importance of adipokines in the complex pathophysiology of RA has been well studied, their specific role in the progression of disease remains to be evaluated [49].…”
Section: Discussionmentioning
confidence: 99%